Kontribusi History Kesultanan Buton Abad 19 Bagi Pendidikan Karakter Generasi Muda Kota Baubau - Muhammad Yusnan; Muhamad Nur Intan Ode; Risky Mullah Muhammad; Asrita; Bayu Lestari (Jayapangus Press, 2023)
Character education in Baubau City has not benefited the current young generation. Thus, the younger generation can use past lessons to strengthen education in the present. The aim of this research is to find out the contribution of the history of the 19th century Buton sultanate to the character education of the young generation of Baubau City. The research method is qualitative research, namely research that does not use numerical calculations and describes the facts found in the field in a structured and systematic way. The main data collection techniques in this study are observation, interviews, and documentation studies. The results of the study show that 1) The contribution of the 19th century Sultanate of Buton to character education for the younger generation regarding ethical values ​​in society is very important and can bring great benefits to individuals and society as a whole, 2) Sultan Muhammad Idrus Kaimudin's strong contribution in strengthening the values ​​of honesty in society, and 3) Sultan Muhammad Idrus Kaimudin's contribution regarding the value of education in society is very large because education does not only provide knowledge, but also forms the character, attitudes, and values ​​needed in social life.